PENGARUH NET PROFIT MARGIN DAN RETURN ON ASSETS TERHADAP KINERJA KEUANGAN POLITEKNIK LP3I JAKARTA KAMPUS CILODONG RAYA - Herni Pujiati; Imelda Maulidina (Institut Teknologi dan Bisnis Swadharma, 2021)
This study aims to examine and analyze the effect of Net Profit Margin and Return On Assets on the Financial Performance of LP3I Polytechnic Jakarta, Cilodong Raya Campus. Data collection was carried out through interviews and requests for financial report data from the LP3I Jakarta Polytechnic, Cilodong Raya Campus in 2015-2018. Data analysis in this study used descriptive analysis and multiple regression analysis with two independent variables. Classical assumption test which includes normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test is used to obtain the feasibility of the regression model. Meanwhile, to answer the research objectives, f test and t-test were carried out on the research hypothesis. The results showed that: (1) The value of t arithmetic > t table (19.381 > 3.18245) and significance <0.05 (0.033 <0.05), then Ho was rejected and Ha was accepted. So it can be concluded that the Net Profit Margin affects the Financial Performance of the Jakarta Polytechnic, Cilodong Raya Campus. (2) The value of t count < t table (-1.504 <3.18245) and significance > 0.05 (0.374> 0.05), then Ho is accepted and Ha is rejected. So it can be concluded that Return On Assets does not affect the Financial Performance of the LP3I Jakarta Polytechnic, Cilodong Raya Campus. (3) Simultaneously and together, Net Profit Margin and Return On Assets affect Financial Performance. This shows that the variables of Net Profit Margin and Return On Assets will simultaneously increase Financial Performance, and vice versa. This is supported by the results of the coefficient of determination with an influence level of 100%.